Application of the genetic algorithms to the identification of the hydrodynamic parameters - Wenddabo Olivier, Sawadogo; Noureddine, Alaa; Kounhinir, Somé; Blaise, Somé (International Journal of Applied Mathematical Research, 2015)
In this work, we propose an adaptation of the algorithm Non-dominated Sorting Genetic Algorithm-II (NSGA-II) proposed by deb. et al. (2002) to solve multi-objective problems to the resolution of mono-objective problem.Contrary to the majority of the genetic algorithms, we did not define a probability of crossing.After having applied our algorithm to functions test, we then used it to identify hydrogeologic parameters where the boundaries values and the source term are supposed to be unknown besides the permeability.The direct problem was solved by using the finite elements of Galerkin on freefem++ and the genetic algorithm was programmed in Matlab. Then we carried out a coupling of the two codes to identify the parameters.
Keywords: Code coupling; Finite elements; Genetic algorithm; Hydrodynamic parameters; Inverse problem.